Antibacterial activity of prenylated benzopyrans from Peperomia obtusifolia (Piperaceae) - Ruiz Mostacero, Nathalie; Castelli, María Victoria; Cutró, Andrea Carla; Hollmann, Axel; Batista, João Marcos; Furlan, Maysa [UNESP]; Valles, Julieta; Fulgueira, Cecilia Luisa; López, Silvia Noelí (My University, 2019)
Peperomia obtusifolia is a herbaceous perennial plant native to the Americas reported as a traditional medicine to treat snake bites and as a skin cleanser. The bioassay-guided fractionation of crude extracts from aerial parts of P. obtusifolia against a panel of clinically important fungi and bacteria, showed that hexane and dichloromethane extracts demonstrated selective bacterial inhibition, allowing the isolation of the known compounds peperobtusin A (1), and 3,4-dihydro-5-hydroxy-2,7-dimethyl-8-(3”-methyl-2”-butenyl)-2-(4’-methyl-1’,3’-pentadienyl)-2H-1-benzopyran-6-carboxylic acid (2) from dichloromethane extract. Compound 2 was active against Gram-positive bacteria including community acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) isolates and an Enterococcus faecalis vancomycin-resistant strain, with minimal inhibitory concentration (MIC) values of 4 μg/mL (10.8 μM) and 8 μg/mL (21.6 μM) respectively. The interaction of compound 2 with the bacterial membrane was demonstrated by means of Zeta potential experiments on S. aureus, then confirming the membrane damage by fluorescent microscopy experiments.
Keywords: antibacterial; CA-MRSA; MRSA; Peperomia obtusifolia; Prenylated benzopyrans; Staphylococcus aureus; zeta potential